Contribution of 2-methyl-3-furanthiol to the cooked meat-like aroma of fermented soy sauce. Issue 1 (2nd January 2017) - Meng, Qi; Kitagawa, Riho; Imamura, Miho; Katayama, Hiroshi; Obata, Akio; Sugawara, Etsuko
Abstract: The cooked meat-like aroma compound, 2-methyl-3-furanthiol (2M3F), was detected in fermented soy sauce (FSS) by GC-olfactometry and GC-MS. 2M3F was present in FSS at a concentration considerably greater than the perception threshold, and the 2M3F concentration increased with heating temperature. Sensory analysis indicated that with the addition of only 0.2 μg/L of 2M3F to the soy sauce sample, the cooked meat-like aroma is significantly stronger than that of sample without the addition of 2M3F. Hence, 2M3F contributes to the cooked meat-like aroma of FSS, which constitutes the key aroma component of FSS. In addition, 2M3F was generated from the addition of ribose and cysteine in FSS by heating at 120 °C, but it was not detected in a phosphate buffer under the same condition. Furthermore, 2M3F was not detected in acid-hydrolyzed vegetable-protein-mixed soy sauce (ASS) and heated ASS. These results indicated that fermentation by micro-organisms facilitates the generation of 2M3F in FSS. Graphical abstract: : 2-methyl-3-furanthiol (2M3F)contribute to the cooked meat-like aroma of fermented soy sauce, and this compound is a very important aroma component of fermented soy sauce.